Houselessness and syringe service program utilization among people who inject drugs in eight rural areas across the USA: a cross-sectional analysis - April M. Ballard; Dylan Falk; Harris Greenwood; Paige Gugerty; Judith Feinberg; Peter D. Friedmann; Vivian F. Go; Wiley D. Jenkins; P. Todd Korthuis; William C. Miller; Mai T. Pho; David W. Seal; et al. (BMC, 2023)
Abstract Background Research conducted in urban areas has highlighted the impact of housing instability on people who inject drugs (PWID), revealing that it exacerbates vulnerability to drug-related harms and impedes syringe service program (SSP) use. However, few studies have explored the effects of houselessness on SSP use among rural PWID. This study examines the relationship between houselessness and SSP utilization among PWID in eight rural areas across 10 states. Methods PWID were recruited using respondent-driven sampling for a cross-sectional survey that queried self-reported drug use and SSP utilization in the prior 30 days, houselessness in the prior 6 months and sociodemographic characteristics. Using binomial logistic regression, we examined the relationship between experiencing houselessness and any SSP use. To assess the relationship between houselessness and the frequency of SSP use, we conducted multinomial logistic regression analyses among participants reporting any past 30-day SSP use. Results Among 2394 rural PWID, 56.5% had experienced houselessness in the prior 6 months, and 43.5% reported past 30-day SSP use. PWID who had experienced houselessness were more likely to report using an SSP compared to their housed counterparts (adjusted odds ratio [aOR] = 1.24 [95% confidence intervals [CI] 1.01, 1.52]). Among those who had used an SSP at least once (n = 972), those who experienced houselessness were just as likely to report SSP use two (aOR = 0.90 [95% CI 0.60, 1.36]) and three times (aOR = 1.18 [95% CI 0.77, 1.98]) compared to once. However, they were less likely to visit an SSP four or more times compared to once in the prior 30 days (aOR = 0.59 [95% CI 0.40, 0.85]). Conclusion This study provides evidence that rural PWID who experience houselessness utilize SSPs at similar or higher rates as their housed counterparts. However, housing instability may pose barriers to more frequent SSP use. These findings are significant as people who experience houselessness are at increased risk for drug-related harms and encounter additional challenges when attempting to access SSPs.